Transformation of the Economic Behavior of Indigenous Coastal Populations in the Tourism Life Cycle of Tanjung Bira, Bulukumba Regency - Ali Anas; Muh. Kafrawi Yunus (Journal of Social and Policy Issues, 2026)
This study aims to analyze the transformation of the economic behavior of indigenous coastal communities within the tourism life cycle of Tanjung Bira by examining changes in livelihood strategies, participation in the informal tourism economy, access to coastal spaces, the role of social capital, adaptive capacity, maritime identity, and local entrepreneurial orientation. The study employed a qualitative approach with an exploratory case study design. Data were collected through in-depth interviews, field observations, documentation, and literature review, and were then analyzed thematically to identify patterns of economic change, forms of adaptation, and the relationship between tourism opportunities and community responses. The findings show that the economic transformation of coastal communities has occurred gradually, nonlinearly, and without completely replacing maritime occupations. Indigenous residents have diversified their livelihoods by combining maritime work, tourism services, informal trade, marine recreation management, and small-scale coastal businesses. These changes are influenced by access to strategic economic locations, family networks, social trust, service skills, work experience in the tourism sector, and the ability to respond to market shifts. Maritime identity is maintained and even converted into cultural capital for developing local tourism products. The study concludes that tourism in Tanjung Bira has created a new economic cycle linking informal work, livelihood diversification, capital accumulation, and the sustainable growth of indigenous coastal entrepreneurship.